Pola pengasuhan di pondok pesantren dalam membentuk karakter mandiri para santri - Zulia Hendriawan; Yuliatin Yuliatin; Ega Anzani (Journal of Education, Cultural and Politics, 2026)
This study discusses the parenting patterns in shaping the independent character of students at Al-Kamal NWDI Islamic Boarding School in Narmada, West Lombok. Using a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation, this study involved informants including the Head of Male Students' Care and the Head of Female Students' Care. The results showed that the parenting pattern applied is a democratic pattern manifested in three integrated domains of students' lives, namely the management of the Al-Kamal Student Organization (OSAKA) which provides space to plan, implement, and evaluate work programs independently; the active involvement of students in various internal committee activities of the Islamic boarding school such as Khazanah, New Student Admission and Welcoming, ESSENSIAL, and OSAKA Replacement; as well as the arrangement of dormitory life through the arrangement of personal belongings and the establishment of a cleaning picket system based on deliberation and mutual agreement. This democratic parenting pattern creates a balance between caregiver guidance and space for students to develop as active subjects capable of making decisions, solving problems, cooperating, and taking responsibility for their actions, thus proving successful in shaping students' independent character in a strong, sustainable, and well-internalized manner.